Using Motion-Graphic Media to Educate Higher Education Students About Depression: A Randomized Controlled Trial - Chookerd, Naparat; Mettarikanon, Dichitchai; Tawanwongsri, Weeratian; Puangsri, Pavarud; Kaeophanuek, Siriwatchana; Boonpit, Veerayut; Wanchai, Adisak (Emerging Science Journal, 2024)
Objective: This study aims to compare the effectiveness of motion graphics versus pamphlets for educating young adults about depression. Methods: A multicenter randomized controlled trial was conducted from April to June 2024; participants were randomly assigned to Group A (motion-graphic media) or Group B (pamphlets) in a 1:1 ratio. Pre- and post-intervention knowledge scores were collected, and satisfaction scores were collected after intervention from group A. Findings: A total of 78 participants with a median age of 19.0 years (IQR 2.0) and predominantly women (64.1%), completed pre- and post-intervention questionnaires. The median knowledge score for Group A increased from 15.0 (IQR 4.0) pre-intervention to 18.0 (IQR 3.0) post-intervention, while Group B's scores improved from 12.0 (IQR 4.0) to 16.0 (IQR 3.0). Post-intervention scores were significantly higher in Group A compared to Group B (p = 0.002). Participants in Group A also reported high satisfaction with the educational material. Novelty:This study highlights the potential of innovative media for patient education, particularly in addressing mental health issues. Long-term cohort studies are required to assess whether this approach can improve clinical outcomes and reduce the incidence of severe depression. Doi: 10.28991/ESJ-2024-SIED1-015 Full Text: PDF